Initial implementation of active learning strategies in large, lecture STEM courses: lessons learned from a multi-institutional, interdisciplinary STEM faculty development program - Emily Borda; Emily Schumacher; Daniel Hanley; Edward Geary; Shannon Warren; Cassidy Ipsen; Lauren Stredicke (SpringerOpen, 2020)
Abstract Background A faculty development program was implemented over four years at a 4-year regional comprehensive university and two partnering community colleges. This project was focused on improving student learning in introductory Science, Technology, Engineering, and Math (STEM) courses at each institution, by helping faculty adopt inclusive, student-centered pedagogies. Survey data were combined with data from classroom videos, faculty interviews, and student questionnaires collected during the first two years of the project to give insight into how faculty initially implemented the theory and strategies they learned and how the students perceived instruction from participating faculty. Results These data sources were combined to generate four overall themes to characterize our project and guide future projects. These are: (1) implementation of student-centered learning took a variety of forms; (2) quality implementation of student-centered teaching practices lagged behind understanding of the theory behind those practices; (3) the most robust perceived barriers to implementation of student-centered teaching stayed constant, while more moderate barriers were ranked differently from year 1 to year 2; and (4) faculty perceptions of student-centered learning practices were not always the same as students' perceptions. These themes build from the extant faculty development literature in that they are drawn from the unique context of a multidisciplinary, multi-institutional project, and that they represent an "on the ground" perspective from case studies combined with "big picture" findings from surveys. Conclusions This paper describes the faculty development project, as well as our collection and interpretation of data from surveys and case studies, to ultimately develop the four themes. Recommendations deriving from these themes are also described. These include modeling a variety of pedagogies; adopting realistic expectations for faculty change; institutionalizing faculty development so it can take place over multiple years; being transparent with faculty about known barriers and aligning supports with those barriers; and helping faculty develop strategies for transparency with students about student-centered pedagogies.